Cooperation, teamwork, and workshops: A proposal to know cultural awareness in Costa Rican classrooms - Chinchilla Jiménez, María Daniela (2025)
This essay explored the concept of human cooperation to achieve specific goals, emphasizing teamwork as a means to foster horizontal relationships that enhance the abilities and knowledge of its members. In this matter, workshops are key strategies that promote collaborative learning, knowledge updating, and skill development by incorporating creativity and innovation, which provide new perspectives and solutions to current social challenges. The proposed workshop presented in this essay focused on the inclusion of cultural diversity in pedagogical practices, with particular emphasis on the province of Limón, Caribbean coast, Costa Rica, a region characterized by its undeniable ethnic, linguistic, and cultural diversity. The objective of the workshop was to encourage teachers to reflect on the integration of culture into the educational setting through the application of various learning theories. This proposal aimed to transform knowledge into concrete actions within educational centers, initiating a cultural integration process. In conclusion, workshops strengthen the transition from group work to teamwork by focusing on common goals, such as raising awareness of cultural diversity. This empowers teachers to become agents of change by incorporating this crucial topic into their pedagogical practices